Klin'-ing up: effects of Polish tax reforms on those in and on those out - Leszek Morawski; Michał Myck (Institute for the Study of Labor (IZA), 2008)
In 2007 and 2008 Polish governments introduced a series of reforms which led to a substantial reduction in the tax wedge (in Polish: klin) on labour. We show that when considered together the package of introduced reforms brought much greater reductions in the tax burden compared to a widely discussed 15% flat tax. In the analysis we show the effects of the reforms both for the employed and for the non-employed populations. The latter analysis is done in such a way as to account for the entire (simulated) distribution of wages of the non-employed and shows interesting differences between the effects of reforms on employed and non-employed individuals. We argue that to fully appreciate the effect of reductions in labour taxation it is important to bear in mind that one of the reasons for introducing them is to make employment more likely for those who currently do not work. Given the extent of the reductions in the klin it is somewhat surprising that so far so little attention has been given to the recent Polish reforms.
urn:nbn:de:101:1-2008111495
Keywords: H24; 330; Work incentives; tax wedge; labour costs; employment; Lohnsteuer; Excess Burden; Steuerreform; Steuerinzidenz; Arbeitskosten; Beschäftigungseffekt; Polen